Multicenter Review of Current Practices Associated With Venous Thromboembolism Prophylaxis in Pediatric Patients After Trauma. Issue 9 (September 2018) - Bigelow, Amee M.; Flynn-O'Brien, Katherine T.; Simpson, Pippa M.; Dasgupta, Mahua; Hanson, Sheila J.
Abstract : Objectives: Frequency of venous thromboembolism in pediatric trauma patients admitted to PICUs is not insignificant, ranging up to 6%. Risk factors have been identified in this population. However, there is little consensus of actual venous thromboembolism prophylaxis practice. We examined factors associated with venous thromboembolism prophylaxis in PICUs. Design: A retrospective study evaluating associations with mechanical venous thromboembolism prophylaxis, pharmacologic venous thromboembolism prophylaxis, or dual therapy (DUAL) prophylaxis compared with no venous thromboembolism prophylaxis. Multivariable logistic regression explored the relationship between prophylaxis type and selected covariates with stepwise selection method to identify the independent predictors of venous thromboembolism prophylaxis utilization. Setting: Five level I/II pediatric trauma centers in the United States. Patients: Children less than 18 years from January 1, 2013, to December 31, 2013, admitted to the PICU after a trauma, identified through combined trauma registry and Virtual Pediatric Systems database. Interventions: None. Measurements and Main Results: Six hundred ninety-two patients were included in the database, with 55 excluded for missing data. Of the remaining 637 patients, 538 (84.5%) had no venous thromboembolism prophylaxis by 48 hours, 77 (12.1%) had only mechanical venous thromboembolism prophylaxis, 11 (1.7%) had DUAL, and 11 (1.7%) had pharmacologic venous thromboembolism prophylaxis alone. Multivariable analysis showed increased age, and orthopedic procedure was associated with all forms of prophylaxis. Orthopedic procedures were associated with higher utilization of dual prophylaxis use (odds ratio, 5.2; 95% CI, 1.2–21.8), pharmacologic venous thromboembolism prophylaxis (odds ratio, 8.5; 95% CI, 2.3–31.7), and mechanical venous thromboembolism prophylaxis (odds ratio, 2.2; 95% CI, 1.1–4.2) alone. Brain/spinal cord procedures (odds ratio, 3.7; 95% CI, 1.9–7.3) and abdominal procedures (odds ratio, 6.6; 95% CI, 2.5–17.1) were associated with mechanical venous thromboembolism prophylaxis. Head injury was associated with a decreased use of any prophylaxis (odds ratio, 0.5; 95% CI, 0.3–0.9). Patient comorbidities were associated with decreased use of mechanical venous thromboembolism prophylaxis (odds ratio, 0.5; 95% CI, 0.3–1.0). Conclusions: Pharmacologic venous thromboembolism prophylaxis is not common in critically ill children after trauma. Patient age, orthopedic and vascular procedures, and higher injury severity are associated with pharmacologic venous thromboembolism prophylaxis.